Introns: The Functional Benefits of Introns in Genomes - Bong-Seok Jo; Sun Shim Choi (Genomics & Informatics)
The intron has been a big biological mystery since it was first discovered in several aspects. First, all of the completely sequenced eukaryotes harbor introns in the genomic structure, whereas no prokaryotes identified so far carry introns. Second, the amount of total introns varies in different species. Third, the length and number of introns vary in different genes, even within the same species genome. Fourth, all introns are copied into RNAs by transcription and DNAs by replication processes, but intron sequences do not participate in protein-coding sequences. The existence of introns in the genome should be a burden to some cells, because cells have to consume a great deal of energy to copy and excise them exactly at the correct positions with the help of complicated spliceosomal machineries. The existence throughout the long evolutionary history is explained, only if selective advantages of carrying introns are assumed to be given to cells to overcome the negative effect of introns. In that regard, we summarize previous research about the functional roles or benefits of introns. Additionally, several other studies strongly suggesting that introns should not be junk will be introduced.